Treatment of acute promyelocytic leukemia in older patients: recommendations of an International Society of Geriatric Oncology (SIOG) task force. Issue 8 (November 2020) - Klepin, Heidi D.; Neuendorff, Nina Rosa; Larson, Richard A.; Hamaker, Marije E.; Breccia, Massimo; Montesinos, Pau; Cordoba, Raul
Abstract: Approximately one third of patients diagnosed with acute promyelocytic leukemia (APL) are above the age of sixty. It is important to ensure older adults receive optimal diagnosis and management since this subtype of acute myeloid leukemia – given appropriate treatment – is highly curable with lower risk of adverse events compared to other types of leukemia. Historically, older age has been a risk factor for early death and poorer overall survival. However, prospects have changed with the introduction of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). APL is curable in the majority of patients regardless of age, and the threshold of fitness that makes ATRA/ATO therapy possible is likely to be lower than for cytotoxic chemotherapy. APL frequently presents as a medical emergency and rapid diagnosis and intervention – typically involving referral to a specialist centre – is a major determinant of outcome. After diagnosis, management of APL in older adults presents particular challenges. Geriatric assessment, including evaluation of frailty, comorbidities and polypharmacy can assist in providing optimal supportive care for older adults during remission induction and may help individualize therapy in the post-remission phase. Here, we review the available evidence, highlighting areas of consensus, gaps in evidence and opportunities for research to enhance diagnosis, management and survivorship for older patients.